The Impact of the DNTK Pattern Approach on Student Learning Outcomes in Introduction to Group Theory Course - Mashuri; St. Budi Waluya; Zaenuri; Isnarto (Hipotenusa: Journal of Mathematical Society, 2025)
Introduction to Group Theory is one of the courses in the field of algebra studies in Mathematics Education Study Program at Universitas Negeri Semarang. Various learning models are implemented in lectures to overcome students' difficulties in understanding and mastering abstract lecture material. In this research, learning was carried out using the DNTK Pattern approach. The DNTK pattern approach is a learning pattern that prioritizes understanding Definitions (D) and their Negations (N), Theorems (T) and their Contrapositions (K) before students are given exercises in the Introduction to Group Theory course. The main goal of this approach is to increase students' conceptual understanding of the structure and properties of groups. This research used quantitative methods and the TAM (Technology Acceptance Model) approach to evaluate the effectiveness of the DNTK pattern approach in improving student learning outcomes. The research results showed that students taught using the DNTK pattern approach have a deeper understanding and are able to apply concepts better compared to conventional learning. This article reviewed the DNTK pattern approach theoretically and empirically, and presented the research results as a basis for further implementation in Introduction to Group Theory lectures.